2014
DOI: 10.3389/fnbeh.2014.00171
|View full text |Cite
|
Sign up to set email alerts
|

Bridging disparate symptoms of schizophrenia: a triple network dysfunction theory

Abstract: Schizophrenia is a complex neuropsychiatric disorder with variable symptomatology, traditionally divided into positive and negative symptoms, and cognitive deficits. However, the etiology of this disorder has yet to be fully understood. Recent findings suggest that alteration of the basic sense of self-awareness may be an essential distortion of schizophrenia spectrum disorders. In addition, extensive research of social and mentalizing abilities has stressed the role of distortion of social skills in schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 107 publications
(150 reference statements)
7
76
0
4
Order By: Relevance
“…In particular, the left SFG is functionally connected to most of the default mode network and suggested to play a key role in information processing between the default mode network and a number of distributed fronto-parietal control networks(54, 55). A series of studies have reported that patients with schizophrenia have exhibited distinct connectivity patterns compared to controls within(56, 57) and between(58, 59) these two networks, each tied to key domains of cognition. The superior frontal gyrus is also among the cortical territories that have vastly expanded, as a proportion of overall cortical tissue, in humans versus other primates(60).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the left SFG is functionally connected to most of the default mode network and suggested to play a key role in information processing between the default mode network and a number of distributed fronto-parietal control networks(54, 55). A series of studies have reported that patients with schizophrenia have exhibited distinct connectivity patterns compared to controls within(56, 57) and between(58, 59) these two networks, each tied to key domains of cognition. The superior frontal gyrus is also among the cortical territories that have vastly expanded, as a proportion of overall cortical tissue, in humans versus other primates(60).…”
Section: Discussionmentioning
confidence: 99%
“…Psychosis and salience attribution deficits in schizophrenia are related to inter-network dysfunction between the SN, CEN and DMN (Palaniyappan et al, 2011, 2013; Moran et al, 2013; Lee et al, 2014; for a comprehensive review, see Nekovarova et al, 2014). Patients experiencing auditory hallucinations show increases in AI and frontal operculum activation and altered SN dynamics, indicating that internally generated stimuli are perceived as abnormally salient (Sommer et al, 2008; Lefebvre et al, 2016).…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…attentional and self-related mental processes) 43 , and mediating the interactions between DMN and CEN 44 . The triple network model has been widely applied to illuminate the brain mechanisms of multiple disorders, including Alzheimer’s disease 45 , schizophrenia 46, 47 , depression 48 , etc. Recently, Abbott and colleagues investigated the iFC of these networks in 37 ASD and 38 typically developed (TD) participants 49 , which was the first research focusing on the three “core” neurocognitive networks in autism.…”
Section: Introductionmentioning
confidence: 99%